An assessment of kangaroo mother care among staff in a specialized neonatal intensive care unit, Asmara, Eritrea - Araya, Elsa Semere (Division of Child and Adolescent Psychiatry, 2019)
Introduction: Preterm delivery remains the major cause of newborn infants’ morbidity and mortality globally and more so in low-income countries like Eritrea. Research has shown that the provision of Kangaroo mother care (KMC) can contribute to a reduction in morbidity and mortality among newborn infants. However, there is limited research on the practice of KMC in Eritrea. Methods: A mixed methods approach was adopted in a phenomenographic study to collect the data. Eleven participants with work experience of at least two years were recruited from the Specialised Neonatal Intensive Care Unit (SNICU) at Orotta Paediatric Hospital (OPH), Asmara, Eritrea. Data were collected via individual interviews and observations. Results: The results showed that participants had no prior KMC training and education. In addition, staff had limited knowledge and mixed attitudes about KMC practice. There were also no KMC guidelines and protocols. Furthermore, space was not adequate for full KMC practice except for implementation of the kangaroo position. The researcher’s observation confirmed similar evidence of a lack of availability of a KMC ward and lack of protocols and guidelines. Limited interaction and communication about KMC between participants and parents was also observed. Some of the most common hindrances to KMC practice were the perception that KMC increased staff work load and that it was time consuming. In addition, lack of regular KMC training for staff, lack of a convenient setup and too few staff members were among the hindrances. One staff members also perceived that KMC practice was not culturally accepted. 15 Conclusion: The results of this study showed that there were no proper KMC guidelines and protocols in the ward. In addition, only the kangaroo position was practiced, not the full KMC protocol. Furthermore, staff had limited knowledge and mixed attitudes. The observation component of the research highlighted the lack of space and KMC protocols and guidelines as key limitations for delivering KMC. Therefore, it is recommended that a programme to improve staff knowledge be implemented, that evidence-based KMC guidelines and polices be made available, that the KMC ward be expanded, and that health education about KMC practice be brought to the population through mass media